With a little help from my friends: Survey-based derivation of euro area short rate expectations at the effective lower bound - Fabian Schupp; Felix Geiger (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
The estimation of dynamic term structure models (DTSMs) turns out to be challenging in the presence of a small sample. It is exacerbated if the sample is characterized by a prolonged period of low interest rates near a time-varying effective lower bound. These challenges all weigh heavily when estimating a DTSM for the euro area OIS yield curve sample. Against this background, we propose a shadow-rate term structure model (SRTSM) that includes a time-varying effective lower bound accounting for the spread between the policy and short-term OIS rate and it also allows for future changes in the effective lower bound. In addition, it incorporates survey information in order to pin down the level of longer-term rate expectations. The model allows to adequately assess short-term monetary policy rate expectations and it generates far-distant rate expectations that are correlated with an estimated equilibrium nominal short rate derived from a macroeconomic model set-up. Our results also highlight the signaling channel of non-standard monetary policy shocks in the run-up to asset purchases based on high frequency identification approach. Our model outperforms DTSM specifications without above modeling features from a statistical and economic perspective. We confirm our findings employing a Monte Carlo simulation.
Keywords: E32; E43; E44; E52; 330; Term structure modeling; short rate expectations; lower bound; survey information; yield curve decomposition; monetary policy; euro area